KSTAR: An algorithm to predict patient-specific kinase activities from phosphoproteomic data - Sam Crowl; Ben T. Jordan; Hamza Ahmed; Cynthia X. Ma; Kristen M. Naegle (Nature Communications, 2022)
Kinases are important drug targets, but predicting their activities from phosphoproteomics data remains challenging. While many existing prediction tools rely on phosphosite-specific quantitative data, Crowl et al. develop a kinase activity prediction algorithm that requires no phosphosite quantification.